The Impact of eConveyancing on Title Registration - Brennan, Gabriel. author. aut Link
XV, 316 p. 7 illus. in color.
Keywords: This work is an assessment of how to manage risk in property transactions in the context of the move from paper-based to electronic conveyancing (eConveyancing). In particular the focus is on risks that impact on title registration, and the security, protection or lack thereof that this registration offers to land owners, third parties and property claimants. The impact is the extent to which a change in the transactional process may unintentionally affect risk (being the consequence of change and the likelihood of that consequence having a negative effect). The risks are identified, analysed and evaluated against the backdrop of title registration and the development of eConveyancing through a comparative analysis of the systems in Ireland and Ontario, while also referencing other developing electronic systems around the globe.